Pertumbuhan dan Ketahanan Penyakit Kepok "Kuning" Pisang Paska Aklimatisasi Bibit di Pembibitan dengan Pupuk Organik Nasa Cair dan Trichoderma - Ratna Nirmala; Ratna Shanti (Jurnal Agroekoteknologi Tropika Lembab, 2019)
Several years ago at 2000 Kepok “Yellow” Banana plantation  in East Kalimantan was attached disease, so that the production was decrease therefor in vitro propogation was a preferred a n alternative method. The aim of this study was to knew the growth and disease resistance of Kepok “Yellow” Banana post acclimatization seedling in nursery giving trichoderma as a biological control technique. This study was conducted in April until July 2018 in Samarinda. The completely randomized factorial was used as experiemental design with two factor ie: giving trichoderma (T) consist two level : with trichoderma (T1) and without trichoderma (T0), another factor ie : giving Nasa liquid organic fertilizer (N), consist four level : N0  (0 ml/l water); N1 (2 ml/l water); N2 (4 ml/l water); N3 (6 ml/l water). So that became 8 treatments, each treatment were repeated for five times.The total population were 40 polybags. Each polybags was planted 1 seedling after post acclimatization  healthy and  strong.  The  parameter  observed    were  increase  of  plant  hight, number of leaves, length of the longest leaves, width of the widest of leaves and diameter of stem. Observation the parameter was every two weeks, except diameter of stem, wich was only the end of observation. Polybag was filled with a mixture of   top soil and goat manure with ratio 4:1. Trichoderma treatment T1 by providing trichoderma agent in mixture top soil. Treatment was done before the seedling planted in the polybag. The treatment of Nasa was done one for week. The result of research showed that the growth of banana seedling have significant different to the treatment of Nasa liquid organic fertilizer, wich was the best concentration N1 (Nasa 2 ml/liter of water. The effect of interaction giving Trichoderma and Nasa, to almost the all of growth parameter were not significant different, except in increase the length of leaves. Al trought it have tendency T1N1  the best effect to the growth of all observation. The proves that the Kepok “Yellow” Banana seedling from tissue culture were fertile growing and healthy without disease attack. Except in treatment without trichoderma on the end observation.Several years ago at 2000 Kepok “Yellow” Banana plantation  in East Kalimantan was attached disease, so that the production was decrease therefor in vitro propogation was a preferred a n alternative method. The aim of this study was to knew the growth and disease resistance of Kepok “Yellow” Banana post acclimatization seedling in nursery giving trichoderma as a biological control technique. This study was conducted in April until July 2018 in Samarinda. The completely randomized factorial was used as experiemental design with two factor ie: giving trichoderma (T) consist two level : with trichoderma (T1) and without trichoderma (T0), another factor ie : giving Nasa liquid organic fertilizer (N), consist four level : N0  (0 ml/l water); N1 (2 ml/l water); N2 (4 ml/l water); N3 (6 ml/l water). So that became 8 treatments, each treatment were repeated for five times.The total population were 40 polybags. Each polybags was planted 1 seedling after post acclimatization  healthy and  strong.  The  parameter  observed    were  increase  of  plant  hight, number of leaves, length of the longest leaves, width of the widest of leaves and diameter of stem. Observation the parameter was every two weeks, except diameter of stem, wich was only the end of observation. Polybag was filled with a mixture of   top soil and goat manure with ratio 4:1. Trichoderma treatment T1 by providing trichoderma agent in mixture top soil. Treatment was done before the seedling planted in the polybag. The treatment of Nasa was done one for week. The result of research showed that the growth of banana seedling have significant different to the treatment of Nasa liquid organic fertilizer, wich was the best concentration N1 (Nasa 2 ml/liter of water. The effect of interaction giving Trichoderma and Nasa, to almost the all of growth parameter were not significant different, except in increase the length of leaves. Al trought it have tendency T1N1  the best effect to the growth of all observation. The proves that the Kepok “Yellow” Banana seedling from tissue culture were fertile growing and healthy without disease attack. Except in treatment without trichoderma on the end observation.